Single-center analysis of patients with frontal fibrosing alopecia: evidence for hypothyroidism and a good quality of life. Issue 2 (February 2019) - Valesky, Eva Maria; Maier, Manuela Denise; Kaufmann, Roland; Zöller, Nadja; Meissner, Markus
Objective: Frontal fibrosing alopecia (FFA) is an underestimated scarring alopecia. This study aimed to examine epidemiological information, as well as predilection sites, associated diseases, and responses to therapy of patients with FFA. We also aimed to determine whether the extent or duration of disease correlated with the quality of life (QoL). Methods: Twelve outpatients with FFA for > 2 years were analyzed. The Erlanger atopic score and the Functional Assessment of Non-life-threatening Conditions (FANLTC) for QoL-assessment were used as scoring systems. Results: All patients were women with a mean age of 70.3 years. Most patients did not have any symptoms during their disease progression and no therapy that was used showed any significant effects. FFA was associated with hypothyroidism. There were no correlations between hairline regression, duration of disease, atopic disposition, and QoL. The overall QoL was good. Conclusions: The present study shows that there is no correlation between the extent of FFA and QoL or atopic predisposition. There is a strong correlation between the incidence of thyroid disease and FFA.